(untitled) (University of Khartoum Journal of Agricultural Sciences, 2023)
The interactive effect of plant density and nitrogen fertilizerlevels on growth and yield of sesame (Sesamum indicum L. cv. Shuak)was investigated under irrigation. The field experiments were conductedduring 2005/06 and 2006/07 seasons in the Experimental Farm of theFaculty of Agriculture at Darmali, Nile Valley University, River NileState, Sudan. Four plant densities (100 000, 150 000, 200 000 and 250000 plants/ha) and three levels of nitrogen fertilizer (0, 22 and 44 kgN/ha) were used. A split-plot design with four replications was used toexecute the experiment. The plants were sown during the first week ofJuly. The results showed that plant height, number of branches per plant,height to first capsule and leaf area index were significantly affected byplant density and level of nitrogen fertilizer. The highest values of thesecharacters were obtained with a plant density of 250 000 plants/ha andtreatment receiving 44 kg N/ha. Increasing plant density significantlydecreased the number of capsules per plant, seed yield per plant andincreased seed yield per unit area. Nitrogen levels significantly increasedseed yield and number of capsules per plant. Significant interaction wasnoted, and the highest seed yield was obtained by the application of 44 kgN/ha at a planting density of 150 000 plants/ha